الإطار التنظيمي لمؤسسات التمويل الأصغر الإسلامي في السعودية : Regulatory Framework for Islamic Microfinance in Saudi Arabia - Oussama Mohamed Al-Ansary; Mohamad, Mohammad Taqiuddin; Mohd Noh, Mohd Shahid (Journal Al-Muqaddimah, 2024)
The research examines the regulatory framework for Islamic microfinance in Saudi Arabia. The research aims to review the government supervisory and regulatory authorities for Islamic microfinance in Saudi Arabia, and to identify the most prominent regulations related to this sector. The research used a descriptive analytical approach, relying on tools for collecting and analyzing qualitative data such as interviews with Islamic microfinance relevant parties, analysis of related reports and documents, as well as benefiting from published reports from the relevant authorities. The research reached a number of findings, including the link between Islamic microfinance and the support of micro-enterprises with the targets of Saudi Vision 2030, the existence of several government supervisory and regulatory authorities for microfinance in Saudi Arabia that work closely to achieve the vision’s targets, such as the Saudi Central Bank and the Social Development Bank, the issuance of numerous regulations related to microfinance in Saudi Arabia, and the existence of two types of Islamic microfinance in Saudi Arabia, including the developmental microfinance led by the Social Development Bank, and the commercial Islamic microfinance through banks and financial institutions supervised by the Saudi Central Bank.